Study on AGC strategy involving the frequency control of HVDC power regulation. (August 2022) - Chen, Gang; Fan, Chengwei; Zhu, Tong; Teng, Yufei; Shi, Huabo; Xiao, Xiong
Abstract: The asynchronous interconnection between the Southwest China power grid (SCPG) and Central China power grid (CCPG) reduces the inertia of rotation of SCPG to 1/5, which leads to a prominent risk of frequency stability. Moreover, in order to suppress the ultra-low frequency oscillations, the parameters of hydropower governors were optimized, which further worsen the frequency regulation capability of the system. Therefore, the frequency control (FC) of high voltage direct current (HVDC) line along with automatic generation control (AGC) are designed to improve the frequency restoration after a large power disturbance. However, the characteristic of FC regulation is contradictory to the subsequent AGC regulation. In order to improve the post-contingency frequency response of power system, an improved AGC strategy is developed. The proposed strategy involves the FC regulation power and distribute the control power according to the characteristics of different generator units. Case study on the actual model of SCPG proves the effectiveness of the strategy.